Assessment of Dietary Diversity and Nutritional Status among Adolescents - Baby Vanlalhruaii (Indian Journal of Nursing Sciences, 2024)
Aim: The study’s objectives were to assess adolescents’ nutritional status and dietary diversity as well as examine the relationships between these variables and a few chosen sociodemographic characteristics. Introduction: To provide the nutrients needed for adolescent physical and cognitive development, dietary diversification is essential. A varied diet during this time promotes healthy growth, lowers the risk of obesity and malnutrition, cultivates wholesome eating habits for the rest of one’s life, and improves general wellbeing. Materials and Methods: 150 teenagers from two Bangalore schools participated in a descriptive cross-sectional study. The number of food groups ingested during the preceding 24 h, according to the nine food groups listed by the food and agriculture organization, was used to calculate dietary variety. A calibrated digital scale and a non-stretchable tape were used to take anthropometric measurements, such as height and weight. The Statistical Packages for the Social Sciences version 2.0 was used to analyze the data. Results: The findings showed that whereas 29.3% of teenagers had low dietary diversity, just 11.3% had great dietary diversity. In addition, 24.7% were overweight, 9.3% were obese, 8% were underweight, and 7.3% were stunted. The nutritional status of adolescents was found to be significantly correlated with the food types and jobs of their moms. Conclusion: The results highlight the need for nutritional interventions to improve the quality of adolescents’ diets, as they show a significant prevalence of malnutrition and insufficient dietary diversity.